The Impact of Tax Planning on Firm Value - Arif Darmawan; Shella Angelina (Pusat P2M Politeknik Negeri Batam, 2021)
The purpose of this research to determine the effect of tax planning that is measured using Cash ETR and Book Tax Difference (BTD) on company value. In addition to that, the purpose of doing tax planning is also to streamline corporate tax expenditures following applicable regulations, so that with the existence of corporate tax planning can estimate the company's tax expenses. This study uses the dependent variable that is the value of the company that is proxy using Tobins' Q while the independent variable is tax planning which is proxy using Cash ETR and Book Tax Different. The control variables used in this study are Size and Leverage. The samples used in this study were all manufacturing sector companies in a row from 2016 to 2018 with a total sample of 135 companies for 3 consecutive years. This study uses the Eviews 9 test tool and uses a multiple regression test. The results of this study indicate that Cash ETR has a positive effect on firm value while Book Tax Different has a negative effect on firm value.